PELATIHAN PEMBUATAN KARYA SENI RUPA MONTASE PADA PESERTA DIDIK KELAS III MIS AL- ANSHAR ALAK - Eta Parera, dkk, Moh. Mul Akbar (ALAINA: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this PKM is to use montage fine arts to develop the creativity of students in class III. The location of the activities was MIS AL-Anshar Alak. The stages of planning, implementing, and evaluating are the methodology employed. The activities' outcomes demonstrate that every student was able to participate in PKM activities with a great deal of zeal and excitement. Students can convey and clarify their thoughts through montages. By showing their friends their montage works, students can improve their language and communication skills. Students can learn to recognize and communicate their emotions through the process of making a montage. Students' self-confidence can rise when they are successful in producing original montage pieces. All things considered, montage exercises can be a useful tool to support the cognitive, motor, elementary school pupils' creative, and social-emotional development.